Temperature dependent quantum cutting in cubic BaGdF5:Eu3+ nanophosphors. (5th January 2021) - Chouryal, Yogendra Nath; Sharma, Rahul Kumar; Ivanovskikh, Konstantin V.; Ishchenko, Aleksey V.; Shi, Qiufeng; Ivanov, Vladimir Yu.; Nigam, Sandeep; Pandey, Archna; Ghosh, Pushpal
Abstract : A task-specific ionic liquid (IL) is employed as a structure directing agent for the synthesis of quantum cutting BaGdF5 :Eu 3+ nanophosphors. Abstract : A task-specific ionic liquid (IL) is employed as a structure directing agent for the synthesis of quantum cutting BaGdF5 :Eu 3+ nanophosphors. Herein, IL and temperature dependent quantum cutting is observed. Maximum (160%) and minimum (123%) quantum cutting efficiencies (QCEs) are obtained in the presence and absence of IL, respectively, at room temperature (295 K). However, at low temperature (10 K), the emission spectrum is dominated by Eu 2+ 5d–4f emission which is further confirmed by X-ray excited luminescence study. It is also observed that decay kinetics recorded for Eu 2+ 5d–4f emission demonstrate longer (with lifetime from 580 ns to 1.5 μs) and faster (with lifetime from 35 to 50 ns) decay components related to normal and surface quenched emission, respectively. In addition, maximum quantum yield ( η = 73.5%) is obtained for the sample prepared in the presence of IL compared to that for the sample prepared without IL ( η = 65%). The easy yet highly phase selective green synthesis of the materials is promising for large scale industrial application in nanothermometry as well as in environmentally benign energy efficient lighting.